No Pain, No Gain: The Effects of Exports on Effort, Injury, and Illness - David Hummels; Jakob R. Munch; Chong Xiang (Institute for the Study of Labor (IZA), 2016)
Increased job effort can raise productivity and income but put workers at increased risk of illness and injury. We combine Danish data on individuals' health with Danish matched worker-firm data to understand how rising exports affect individual workers' effort, injury, and illness. We find that when firm exports rise for exogenous reasons: 1. Workers work longer hours and take fewer sick-leave days; 2. Workers have higher rates of injury, both overall and correcting for hours worked; and 3. Women have higher sickness rates. For example, a 10% exogenous increase in exports increases women's rates of injury by 6.4%, and hospitalizations due to heart attacks or strokes by 15%. Finally, we develop a novel framework to calculate the marginal dis-utility of any non-fatal disease, such as heart attacks, and to aggregate across multiple types of sickness conditions and injury to compute the total utility loss. While the ex-ante utility loss for the average worker is small relative to the wage gain from rising exports, the ex-post utility loss is much larger for those who actually get injured or sick.
Keywords: I1; F1; J2; F6; 330; demand shocks; worker effort; health